Current Understanding of Apoptosis - Programmed Cell Death - Yusuf Tutar (IntechOpen, 2018)
Apoptosis is an essential biochemical process in cell turnover, development, and chemical-induced cell death. Current knowledge and ongoing research of apoptosis highlight our understanding in designing the therapeutic approaches for several diseases. This book covers four main sections: ""Apoptosis and Necrosis,"" ""Apoptosis Inducers,"" ""Proteasome and Signaling Pathways in Apoptosis,"" and ""Radiation-Based Apoptosis."" The first section implicitly describes the differences between apoptosis and necrosis processes. The following section elaborates the small molecule-induced apoptosis. Then, the third section deals with proteasome and signaling pathways and finally, resistance to chemotherapy and electromagnetic radiation is covered in the last section. Overall, the book deals with pathways for manipulating apoptosis and provides a unique perspective to the scientists.
English
Keywords: Medicine; Health Sciences; Cell Biology